Postcards from Another's Home: Visual Dialogues for Cultural Tolerance - Silverman, Jonathan (Art education (Reston), 2007)
In the following discussion I use direct quotes from students in the class, insert scholarly references to illustrate points, and address broad implications both for art educators and for learning.3 Aesthetic Inquiry The postcards from the Fleming Museums exhibition offered us a rich source for aesthetic inquiry.4 Our observation of the exhibit's mostly 4'' x 6'' postcards led to an examination of the visual text of buildings, maps, clothes, leisure, and contemporary technology to form our own images of another place. An elementary art teacher commented that the process of researching context of another's story became a template for her research of other artwork and visual images (personal communication, February 17, 2005).\n Curriculum such as "Postcards from Anofher's Home" created opportunities for students to cultivate new perspectives, engage in the search for social vision, imagine multiple vantage points, and reflect on one's own emerging narrative (Greene, 1995).